If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -12 = 5y + -10 Reorder the terms: -12 + 6y = 5y + -10 Reorder the terms: -12 + 6y = -10 + 5y Solving -12 + 6y = -10 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -12 + 6y + -5y = -10 + 5y + -5y Combine like terms: 6y + -5y = 1y -12 + 1y = -10 + 5y + -5y Combine like terms: 5y + -5y = 0 -12 + 1y = -10 + 0 -12 + 1y = -10 Add '12' to each side of the equation. -12 + 12 + 1y = -10 + 12 Combine like terms: -12 + 12 = 0 0 + 1y = -10 + 12 1y = -10 + 12 Combine like terms: -10 + 12 = 2 1y = 2 Divide each side by '1'. y = 2 Simplifying y = 2
| -3-(8x-4)=3(x+2)+7 | | -14x+7=21 | | -x-2(x+1)=1-7x | | 3(2x+8)=2(2x+40) | | 10x-7y=44 | | 5+2(x+3)=-x-6 | | 0=t^2+t-6 | | a+5=-16 | | -3(5+7p)=33-5p | | -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx | | 0=a^2-18a+72 | | 4x+6=-7x-7 | | -15t^2+60t=0 | | 5t+6-8t=30 | | 24t^2+19t+2=0 | | .25p+7=3 | | (2x^2-5x-3)=0 | | 2q+30=6-4q | | 50x=20x+10 | | 3x+5+6x=113 |